Função de resposta fiscal e sustentabilidade da política fiscal dos municípios cearenses - Brito, Lucio Vieira de (2009)
A lot of studies indicate that the Brazilian public debt is solvent. However, the analysis of this issue at the municipal level still leaves much to be desired. The latest methods to test this problem involve the estimation of fiscal reaction function of government. But how can the state of Ceará have behaved in relation to public debt and primary surplus? This study uses panel data to estimate the fiscal response function for three groups of data consisting of municipalities of Ceará in the period 2002 to 2008, with the first group comprises a composite sample of 147 municipalities with no differentiation between the wealthier and poorer. The second is composed of 37 municipalities and the richest third and final group analyzed a sample consisting of the 37 poorest municipalities of the state. This reaction function is estimated by three different methods: OLS Pooled (OLSP), fixed effect model (FE) and random effect model (RE). It was noticed that in all models estimated the condition of solvency of public debt is satisfied. Keywords: